Business Strategy in Islamic Boarding School: A Case Study of Pesantren Hidayatullah Depok Indonesia - Kintan Nur Ramadini; Neneng Hasanah; Mohammad Iqbal Irfany (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2023)
Purpose: This study aims to identify the strengths, weaknesses, opportunities, threats, and strategic priorities in the development of a business unit in a pesantren, a culturally rooted Islamic boarding school in Indonesia. Methodology: Employing ANP-SWOT analysis, this study indicates that strengths and opportunities are the main priorities in developing pesantren’s business unit. The most influential aspects of strengths, weaknesses, opportunities, and threats are cooperation with internal and external parties in developing business and marketing management that is not optimal. Results: Islamic boarding schools can play a more important role in economic activities as producers that meet community needs, in particular, and even supply a broader market. The most important strategy is to improve the quality of human resources by improving the mindsets and skillsets of business activities. Conclusions: Pesantren Hidayatullah Depok develop economic independence through student- and community-involved business units, leveraging social capital, improving HR quality, governance, marketing, and networking, while future research can explore diverse pesantrens to comprehensively understand their role in community-based economic development. Limitations: This study is limited by its focus on only one pesantren case, which may not fully represent the diversity of business strategies across different types of pesantrens in Indonesia. Contributions: This research contributes to understanding how pesantren business units can achieve economic independence by leveraging social capital and strategic human resource development. Novelty: The study offers a novel insight by integrating Analytic Network Process-Strengths, Weaknesses, Opportunities, and Threats (ANP-SWOT), analysis to identify strategic priorities specifically tailored for pesantren business unit development.